2014
DOI: 10.1002/chem.201304593
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Iron Complexes as Efficient Catalysts for “Green” Atom‐Transfer Radical Polymerization of Styrene, Methyl Methacrylate, and Butyl Acrylate with Low Catalyst Loadings and Catalyst Recycling

Abstract: Environmentally friendly iron(II) catalysts for atom-transfer radical polymerization (ATRP) were synthesized by careful selection of the nitrogen substituents of N,N,N-trialkylated-1,4,9-triazacyclononane (R3 TACN) ligands. Two types of structures were confirmed by crystallography: "[(R3 TACN)FeX2 ]" complexes with relatively small R groups have ionic and dinuclear structures including a [(R3 TACN)Fe(μ-X)3 Fe(R3 TACN)](+) moiety, whereas those with more bulky R groups are neutral and mononuclear. The twelve [(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…Alkyl amines with mono or multidentate coordinating sites or bipyridine derivatives were used for conducting iron ATRP [19,[44][45][46][47]. A series of Fe II complexes with N,N,N-trialkyl-1,4,9triazacyclononane (TACN) ligands were investigated in ATRP [48][49][50][51]. The complexes formed either a mononuclear iron species in the presence of TACN ligands substituted with bulky groups, or trinuclear ionic species with a cationic dinuclear and an anionic mononuclear complex in the presence of less bulky substitution groups to form coordinatively saturated compounds.…”
Section: Nitrogen-based Ligandsmentioning
confidence: 99%
“…Alkyl amines with mono or multidentate coordinating sites or bipyridine derivatives were used for conducting iron ATRP [19,[44][45][46][47]. A series of Fe II complexes with N,N,N-trialkyl-1,4,9triazacyclononane (TACN) ligands were investigated in ATRP [48][49][50][51]. The complexes formed either a mononuclear iron species in the presence of TACN ligands substituted with bulky groups, or trinuclear ionic species with a cationic dinuclear and an anionic mononuclear complex in the presence of less bulky substitution groups to form coordinatively saturated compounds.…”
Section: Nitrogen-based Ligandsmentioning
confidence: 99%
“…Iron is also the most abundant metal on earth making it relatively cheap; these characteristics have initiated a lot of research and interest in Fe catalyzed organic chemistry, including ATRP, in line with the perspectives of "green chemistry" [66,67]. The choice of the ligand is a complex question; it depends on the nature of the polymer and the catalyst used [68]: for example, pentamethyldiethylenetriamine (PMDETA) can be used in combination with Cu [69], and tris(3,6-dioxaheptyl) amine (TDA) with Fe [70]. Furthermore, the activators regenerated by electron transfer (ARGET) ATRP, developed by Matyjaszewski et al diminish the amount of catalyst needed (< 50 ppm) [71,72].…”
Section: Grafting Techniques 321 Atom Transfer Radical Polymerizatmentioning
confidence: 99%
“…However, the controllability was poor when [sadim]FeCl 2 60 complex was used as catalyst and AIBN as initiator for reverse ATRP of styrene (M w /M n ~ 2.0). Nagashima et al 48, 293, 294 reported a variety of reusable and environmentally friendly "green" ionic trinuclear iron catalysts bearing nitrogen substituents of triazacyclononane (tcan) ligands 65 for…”
Section: Isolated Iron Complexesmentioning
confidence: 99%